An application of semi-infinite programming to air pollution control - Vaz, A. Ismael F. (2007)
Environment issues are more then ever important in a modern society. Complying with stricter legal thresholds on pollution emissions raises an important economic issue. This talk presents some ideas in the use of optimization tools to help in the planning and control of non mobile pollution sources. We assume a Gaussian plume model where a plume rise and weather stabilities classes are considered. Three main semi-infinite programming formulations are described and numerical results are shown.